Long-working-distance Raman system for monitoring of uPA ECR CVD process of thin diamond/DLC layers growth - Gnyba, Marcin; Kozanecki, Marcin; Wroczyński, Piotr; Kosmowski, Bogdan B; Bogdanowicz, Robert (Photonics Letters of Poland, 2009)
Development of the optoelectronic system for Raman spectroscopic monitoring of diamond/DLC (Diamond-Like-Carbon) thin films growth during uPA ECR CVD (Microwave Plasma Assisted Electron Cyclotron Resonance Chemical Vapour Deposition) process is described. Modular system for non-invasive in-situ monitoring equipped with fibre-optic probes was designed and tested. The most significant parameters of the deposited films like their molecular composition, presence of defects and rate of the film growth will be studied. Investigations with use of optoelectronic tools will provide important data about CVD process progress as well as would enable optimization of its parameters and improvement of synthesized films quality.